The Relationship of Teaching Style to Student Learning Outcomes in Class V Mathematics Learning - Daitin Tarigan; Sandiolonia Sihotang (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to find out whether there is a significant relationship between the teacher's teaching style and the improvement of mathematics student learning outcomes in class V SD N 06 Salaon Toba. This research is a correlational study. The research sample used total sampling, namely all fifth grade students at SDN 06 Salaon Toba as many as 30 people. Data collection in this study was carried out using questionnaires and tests. The data analysis technique uses the product moment correlation formula and t-test. The results of this study indicate that the teaching style of teachers at SDN 06 Salaon Toba is in the High category where the average score is 103.77 while student learning outcomes are in the high category with an average score of 87.66. The teacher's teaching style greatly influences student learning outcomes in Mathematics. It can be seen from the calculation results that rcount is 0.501 while rtable = 0.361, so rcount > rtable. While the value of tcount = 3.063204, ttable value = 2.04841. By comparing the two prices, tcount > ttable is obtained. Thus, it can be concluded that the hypothesis which states that there is a significant relationship between the Teacher's Teaching Style and the Improvement of Student Learning Outcomes in Mathematics Learning in Class V SDN 06 Salaon Toba can be accepted.